Penerapan Model Project Based Learning ( PjBL ) dengan Media Animasi untuk Meningkatkan Motivasi Siswa SMK PAB 1 Helvetia - Lisnawati Lisnawati; Disna Anum Siregar (Journal on Education, 2025)
This Classroom Action Research was conducted on students of class XI Mechanical Engineering-2 SMK PAB Helvetia Medan due to low learning motivation, where only 40% of students achieved a score of ≥75. The objectives of this study are: 1) To determine the application of the Project Based Learning (PJBL) Learning model with animation media can increase learning motivation in class XI SMK PAB 1 Helvetia. 2) To determine how to apply the Project Based Learning (PJBL) Learning model with animation media can increase student learning motivation in class XI SMK PAB 1 Helvetia. 3) To determine learning motivation in class XI SMK PAB 1 Helvetia Medan when the Project Based Learning (PJBL) learning model with animation media is applied. The research method used is Classroom Action Research (CAR). The research was conducted in three cycles, each cycle consisting of planning, implementation of actions, observation, reflection. The subjects of this study were 32 students of class XI Mechanical Engineering-2. Data collection used in this study was qualitative and quantitative data. The results obtained from this study include the learning motivation of class XI Mechanical Engineering students of SMK Swasta PAB 1 Medan Helvetia when the project based learning model is applied. The study was conducted in three cycles, with 32 students as subjects. Data were collected qualitatively and quantitatively. The results showed an increase in learning motivation: the average value increased from 74.6 (cycle I) to 84 (cycle II), and 90.32 (cycle III). The percentage of students with high motivation increased from 12.5% ​​(cycle I) to 81.25% (cycle III). Because it had reached a success indicator of ≥75%, the implementation of PJBL was stopped, showing its effectiveness in increasing student learning motivation.